Effect of radiotherapy on the radiopacity and flexural strength of a composite resin. - Catelan, Anderson; Padilha, Ana C S; Salzedas, Leda Maria Pescinini [UNESP]; Coclete, Gilberto Aparecido [UNESP]; Santos, Paulo Henrique dos [UNESP] (My University, 2008)
The aim of this study was to evaluate the effect of radiotherapy on the radiopacity and flexural strength of composite resin. Forty Z250 composite resin specimens were polymerized using a halogen light-curing unit and divided into 5 groups, in accordance with the radiotherapy dose: G1- without irradiation, G2- 30 Gy, G3- 40 Gy, G4- 50 Gy and GS- 60 Gy Digital images were obtained using a GE 100 X-ray. Radiopacity values were obtained with the Digora digital imaging system and the flexural strength was evaluated with an EMIC universal testing machine. Data were submitted to ANOVA and Tukey 's test. G1 presented the highest radiopacity value, followed by G3, G5, G4 and G2. For flexural strength, G1 presented the lowest value, followed by G2, G5, G3 and G4. Differences were no significant (p>0.05). The commonly used dosage of radiotherapy treatment, did not cause alteration in the radiopacity and flexural strength of resin-based composites.
Keywords: biomedical and dental materials; contrast medium; Filtek Z250; polymer; resin; chemistry; dental care; dental curing light; human; instrumentation; materials testing; mechanical stress; photon absorptiometry; pliability; radiation dose; radiation exposure; radiotherapy; tooth radiography; Absorptiometry, Photon; Composite Resins; Contrast Media; Curing Lights, Dental; Dental Materials; Dental Stress Analysis; Humans; Materials Testing; Pliability; Polymers; Radiography, Dental, Digital; Radiotherapy; Radiotherapy Dosage; Stress, Mechanical